2019
DOI: 10.1016/j.stem.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A Homeostatic Arid1a-Dependent Permissive Chromatin State Licenses Hepatocyte Responsiveness to Liver-Injury-Associated YAP Signaling

Abstract: Highlights d Arid1a expression in hepatocytes promotes liver regeneration after periportal injuries d Arid1a endows a permissive chromatin state to liverprogenitor-like cell-enriched genes d Arid1a-dependent permissive chromatin defines responsiveness to regenerative signals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 66 publications
3
93
0
Order By: Relevance
“…When cultured in vitro, both LPLCs and their duct cell-like progeny were capable of selfrenewal [28,29], further supporting the progenitor proprieties of these LPLCs. Notably, hepatocyte to LPLC dedifferentiation was not induced in pericentral liver injury [30]. Other studies have shown the contribution of biliary epithelial cell-derived oval cells to hepatocyte regeneration, mainly through labeling Foxl1 + and Lgr5 + cells during liver injury [32,33].…”
Section: Trends In Cell Biologymentioning
confidence: 86%
See 4 more Smart Citations
“…When cultured in vitro, both LPLCs and their duct cell-like progeny were capable of selfrenewal [28,29], further supporting the progenitor proprieties of these LPLCs. Notably, hepatocyte to LPLC dedifferentiation was not induced in pericentral liver injury [30]. Other studies have shown the contribution of biliary epithelial cell-derived oval cells to hepatocyte regeneration, mainly through labeling Foxl1 + and Lgr5 + cells during liver injury [32,33].…”
Section: Trends In Cell Biologymentioning
confidence: 86%
“…were found to dedifferentiate into liver progenitor-like cells (LPLCs), expressing both hepatocyte and biliary epithelial cell markers, particularly SOX9, a putative LPC marker [27][28][29]. Remarkably, hepatocyte-derived LPLCs contributed to nearly 20% of newly regenerated hepatocytes in vivo [30]. Moreover, the LPLCs generated duct-like cells when liver injury was prolonged [27,29,31].…”
Section: Trends In Cell Biologymentioning
confidence: 99%
See 3 more Smart Citations